Sme and innovation in automation: the influence of family goals - Bannò, Mariasole; D'Allura, Giorgia Maria; Filippi, Emilia; Trento, Sandro (Piccola Impresa / Small Business, 2022)
Purpose. The paper examines whether, on the basis of Socio Emotional Wealth (SEW), family SMEs differ from non-family firms in their propensity to innovate in automation. Design/methodology/approach. Built on SEW, we hypothesise that family firms, especially SMEs, differ from non-family SMEs, in two needs: (a) the care for their employees and (b) the preservation of the image and reputation of the family and the firm in the community. The empirical analysis is based on a sample of 3,618 Italian SMEs and adopts the two-stage procedure proposed by Heckman (1976, 1979). Findings. Consistent with the SEW perspective, family SMEs are less inclined to innovate in automation. Practical and Social implications. The evidence of this study could be used to design policies that promote the innovation and application of automation by helping family SMEs to evaluate the positive and negative aspects and to overcome any resistance due to the influence of socio-emotional endowment on strategic decisions. From a managerial point of view, the critical issues that family SMEs face when deciding to innovate in automation are highlighted. Originality of the study. For the first time it is analysed how much family involvement affects the strategic decision to innovate in automation in SMEs by applying SEW.